Heartless Rulez! Mechanical objectivity, empathic understanding, and the permissibility of AI - Patrick Schenk (Frontiers in Sociology, 2025)
Sociologists have generally stressed AI’s capacity to make processes mechanically objective as a major justification for its use in modern societies. Psychologists, in contrast, have emphasized AI’s lack of empathic understanding as a major barrier for its moral acceptance. From the perspective of mechanical objectivity, a process is considered legitimate and fair if it maximizes consistency through the impersonal application of rules. Coming from empathic understanding, a purely mechanically objective process is inflexible, deterministic, and heartless. Mechanical objectivity and empathic understanding are thus in tension. This paper empirically analyzes the impact of mechanical objectivity, empathic understanding, and their interplay with an individual’s general orientations for permissibility judgments on the use of AI as an adjudicating entity in criminal courts. In a survey experiment with 793 students in Switzerland, I find that both concepts causally impact permissibility. Yet, social orientation significantly moderates the effect of empathic understanding. Socially oriented individuals are thus particularly skeptical of AI as an adjudicating entity because of its deficit to emphasize with others. The study demonstrates the importance of theorizing the interplay between cultural concepts and internalized orientations to explain the impact of normative ideals on the acceptance of AI, bringing sociological and psychological research into conversation.